Efficient estimation of effective hydraulic properties of stratal undulating surface layer using time-lapse multi-channel GPR - Pan, Xicai; Roth, Kurt (Hydrology and earth system sciences, 2019)
Abstract. Multi-scale soil architectures in shallow subsurface are widespread in natural and anthropogenic depositional environments, and acquisition of the surface stratal structure and hydrological properties are essential in quantifying water cycling. Geophysical methods like ground-penetrating radar (GPR) can provide quantitative information like soil architecture and spatiotemporal soil water content distribution for the shallow layer. Concerning the informative multi-dimensional water flow in the surface layer with an undulating bottom at the plot scale, this study assesses the feasibility of efficiently estimating soil hydraulic properties using a few time-lapse multi-channel GPR observations, namely soil water storage and layer thickness of the surface layer, at reclamation land near an old river channel. We show that effective hydraulic properties of the surface layer can be obtained with a small number of time-lapse GPR measurements during a rainfall event. Additionally, we analyze the effect of some key factors controlling the informative lateral water redistribution on the results of the proposed approach using synthetic simulations.
Gesehen am 30.10.2019